The Effect of Work Environment and Work Discipline on Employee Performance Through Motivation - Fauziah, Sofi Idianti; Baskara, Ika (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The role of human resources depends on employees' ability to plan, manage and produce useful contributions to achieve company goals. This research aims to determine the influence of the work environment and work discipline on employee performance which is moderated by motivation. This research was conducted at PT Persada Gading Elok using a questionnaire and distributed to 100 employees with saturated sampling. Data analysis uses smartPLS 3.2.9 and this research method uses Structural Equation Modeling (SEM) so that the research results are known to have a direct influence on the work environment on employee performance, and work discipline influences employee performance, and motivation influences employee performance, while motivation moderates the work environment on employee performance and motivation moderates work discipline on employee performance. This research has implications for organizations to play a big role in providing welfare for their employees so that their performance is more optimal and the company progresses.